1984
DOI: 10.1159/000153452
|View full text |Cite
|
Sign up to set email alerts
|

Human Red Cell Esterase D Polymorphism in Denmark, Its Use in Paternity Cases and the Description of a New Phenotype

Abstract: Red cell esterase D (EsD) phenotypes were determined in a Danish population sample of 3,116 unrelated adults by starch-gel electrophoresis. A new phenotype was discovered, which appeared to be determined by the EsD1 allele and a new allele EsDcPh. The gene frequencies observed were EsD1 = 0.9007, EsD2 = 0.0992, EsDCPh = 0.0001. Investigation of 1,111 mother-child pairs and 59 families with 157 offspring added further support to the genetic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Additional rare alleles have subsequently been reported: EsD*3 (Bender and Frank 1974), EsD*4 (Berg et al 1976), EsD*6 (Radam et al 1980), EsD*7 (Siege and Schwehn 1983), EsD*Cph (Dissing and Heriksen 1984), EsD*D (Henke and Basler 1984), EsD*B (Gradl et al 1985). Nishigaki and Itoh (1984) found EsD*7 to be polymorphic in Japan, but this allele could be not identical with the independently discovered European EsD*7.…”
Section: Introductionmentioning
confidence: 99%
“…Additional rare alleles have subsequently been reported: EsD*3 (Bender and Frank 1974), EsD*4 (Berg et al 1976), EsD*6 (Radam et al 1980), EsD*7 (Siege and Schwehn 1983), EsD*Cph (Dissing and Heriksen 1984), EsD*D (Henke and Basler 1984), EsD*B (Gradl et al 1985). Nishigaki and Itoh (1984) found EsD*7 to be polymorphic in Japan, but this allele could be not identical with the independently discovered European EsD*7.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed the existence of a number of rare alleles in various populations: EsD*3 (Bender and Frank 1974), EsD*4 (Berg et al 1976), EsD*Mamelodi (Hitzeroth et al 1976), EsD*0 (Marks et al 1977), EsD*3Negrito (Omoto et al 1978), EsD*3-1 (Suzuki et al 1978), EsD*5 (Martin 1979), EsD*6 (Radam et al 1980), EsD*7 (Siege and Schwehn 1983), EsD*Copenhagen (Dissing and Eriksen 1984), EsD*Diisseldorf (Henke and Basler 1984), and EsD*Yamaguchi (Yuasa et al 1985b). Using isoelectric focusing, the EsD*5 allele was later shown to be relatively common in white people, while the EsD*7 allele was reported to occur with appreciable frequency in Japanese by Nishigaki and Itoh (1984).…”
mentioning
confidence: 99%